From Hierarchies to Levels: New Solutions for Games - Mikel Álvarez-Mozos; René van den Brink; Gerard van der Laan; Oriol Tejada (Tinbergen Institute, 2015)
Recently, applications of cooperative game theory to economic allocation problems have gained popularity. In many of these problems, players are organized according to either a hierarchical structure or a levels structure that restrict players possibilities to cooperate. In this paper, we propose three new solutions for games with hierarchical structure and characterize them by properties that relate a players payoff to the payoffs of other players located in specific positions in the structure relative to that player. To define each of these solutions, we consider a certain mapping that transforms any hierarchical structure into a levels structure, and then we apply the standard generalization of the Shapley Value to the class of games with levels structure. The transformations that map the set of hierarchical structures to the set of levels structures are also studied from an axiomatic viewpoint by means of properties that relate a players position in both types of structure.
Keywords: C71; 330; TU-game; hierarchical structure; levels structure; Shapley Value; axiomatization